2022
DOI: 10.1002/jmri.28281
|View full text |Cite
|
Sign up to set email alerts
|

Subcutaneous Adipose Tissue Edema in Lipedema Revealed by Noninvasive 3T MR Lymphangiography

Abstract: Background Lipedema exhibits excessive lower‐extremity subcutaneous adipose tissue (SAT) deposition, which is frequently misidentified as obesity until lymphedema presents. MR lymphangiography may have relevance to distinguish lipedema from obesity or lymphedema. Hypothesis Hyperintensity profiles on 3T MR lymphangiography can identify distinct features consistent with SAT edema in participants with lipedema. Study Type Prospective cross‐sectional study. Subjects Participants (48 females, matched for age [mean… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 38 publications
0
13
0
1
Order By: Relevance
“…Eight studies reported on MRI and three studies compared lipedema and lipolymphedema patients 7,16,29–34 . Lohrman and Duewell et al 7,34 did not specify criteria for diagnosing lipedema.…”
Section: Resultsmentioning
confidence: 99%
“…Eight studies reported on MRI and three studies compared lipedema and lipolymphedema patients 7,16,29–34 . Lohrman and Duewell et al 7,34 did not specify criteria for diagnosing lipedema.…”
Section: Resultsmentioning
confidence: 99%
“…Additional structural and molecular imaging techniques (e.g., high spatial-resolution T1- and T2-weighted MRI, sodium Na23-MRI, H1 relaxometry) and statistical image analysis approaches (e.g., texture quantification) are being investigated to develop discriminative, noninvasive MRI biomarkers of lipedema. Recently, vascular imaging revealed unique spatial patterns of fluid retention in lipedema SAT and could be incorporated into a multimodal imaging approach to disambiguate potential vascular etiology of SAT deposition 25 . The relationship of such radiological biomarkers to clinical symptomatology and functional impairments is also of interest to better understand the complex disease mechanisms of lipedema.…”
Section: Discussionmentioning
confidence: 99%
“…These features seen on imaging exams allow for differentiation from other conditions like phlebedema or lipidema, which can be clinically challenging. [90][91][92] Grading systems that take into account the degree of fat and fluid contributions to extremity swelling in chronic lymphedema would assist in determining whether a patient could undergo debulking vs. direct lymphatic repair. 86 Microreconstruction planning can require a detailed assessment of regional lymph node characteristics and precise depiction of the lymphatic system including number, diameter, and location.…”
Section: Mri Staging Systems and Reporting For Lymphedemamentioning
confidence: 99%
“…8). These features seen on imaging exams allow for differentiation from other conditions like phlebedema or lipidema, which can be clinically challenging 90–92 . Grading systems that take into account the degree of fat and fluid contributions to extremity swelling in chronic lymphedema would assist in determining whether a patient could undergo debulking vs. direct lymphatic repair 86 …”
Section: Lymphatic Imagingmentioning
confidence: 99%